Youth wellbeing and its determinants in the occupied Palestinian territory. (March 2019) - Khatib, Ahmad; Hammoudeh, Weeam
Abstract: Background: Young people in the occupied Palestinian territory are facing considerable challenges that affect their wellbeing. As limited research on youth wellbeing in this region exists, this study aims to assess the prevalence of wellbeing and its determinants among youths in the occupied Palestinian territory. Methods: We carried out a secondary data analysis of the Power2Youth cross-sectional survey, conducted between Oct 13, 2015 and Dec 31, 2015 in the occupied Palestinian territory. The sample consisted of 1353 youths aged 18–29 years (53.8% were female) living in the West Bank and the Gaza Strip. Bivariate and multivariate analyses were conducted with the WHO-5 Well-Being Index as the dependent variable and seven independent variables: demographic (age, sex, locality, and region), socioeconomic status (education and subjective economic situation scale), trust in people, personal freedom, political confidence, satisfaction with the quality of governance, and future outlook. Informed verbal consent was obtained from the participants. Findings: The mean wellbeing score was 58·73 (SD 22·7). Age (β=–0·60, p=0·01) and being male were negatively associated with wellbeing, with male scores approximately three points lower than for females on the wellbeing scale (β=–2·80, p<0·05). By contrast, living in camp areas compared to urban areas (β=4·45, p<0·01), trust in people (β=1·92, p<0·001), personal freedom (β=2·02, p<0·001), satisfaction with the quality of governance (β=2·36, p<0·001), satisfaction with economic conditions (β=1·61, p<0·001) and positive future outlook (β=0·67, p<0·01) were all significantly positively associated with wellbeing. Interpretation: The results underscore the impact of demographic, social, economic, and political circumstances on youth wellbeing in the occupied Palestinian territory, with trust in people, personal freedom, and satisfaction with economic conditions having the greatest impact. These variables and satisfaction with the quality of governance were found to have a significant positive association with youth wellbeing, highlighting the importance of the political domain. Finally, the positive association between outlook and wellbeing indicates that youths' future outlook can impact wellbeing in the present. Funding: The research that produced the Power2Youth dataset received funding from theEuropean Union's Seventh Framework Programme (FP7/2007-2013 ) under grant agreement number 612782. Analysis and production of the Abstract was supported by Oxfam Quebec.